2014
DOI: 10.1080/07294360.2014.892477
|View full text |Cite
|
Sign up to set email alerts
|

Does higher education foster critical and creative learners? An exploration of two universities in South Korea and the USA

Abstract: This paper describes two studies that explore students' beliefs about critical and creative learning at two universities, and considers the implications of those beliefs in comparison to the universities' stated education goals. One is a mixed method study of students at a top university in Korea, and the second is a comparative study between the Korean university and a United States (US) university. The first study found that both high-achievers and the general population at a top Korean university perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 22 publications
0
23
0
2
Order By: Relevance
“…It is well-documented that the English education in the Korean public-school system is focused heavily on the tests such as the College Scholastic Aptitude Test (csat) that are heavily focused on lower order thinking skills (Choi, 2012;Jeon, 2010;Kim, Hutchinson, & Hall, 2015). Even at the post-secondary level, studies reveal that higher level cognitive dimensions of evaluating (checking and making judgments) and creating (planning, generating, and producing) are much less commonly emphasized (Lee, Lee, Makara, Fishman, & Hong, 2014;Baek, 2016). Writing courses, for example, have been criticized for being excessively product focused and lacking in the feedback which is essential to supporting individuals in the development of process-based writing skills (Kim & Kim, 2005).…”
Section: English Language Production In the Korean University Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-documented that the English education in the Korean public-school system is focused heavily on the tests such as the College Scholastic Aptitude Test (csat) that are heavily focused on lower order thinking skills (Choi, 2012;Jeon, 2010;Kim, Hutchinson, & Hall, 2015). Even at the post-secondary level, studies reveal that higher level cognitive dimensions of evaluating (checking and making judgments) and creating (planning, generating, and producing) are much less commonly emphasized (Lee, Lee, Makara, Fishman, & Hong, 2014;Baek, 2016). Writing courses, for example, have been criticized for being excessively product focused and lacking in the feedback which is essential to supporting individuals in the development of process-based writing skills (Kim & Kim, 2005).…”
Section: English Language Production In the Korean University Contextmentioning
confidence: 99%
“…These finds should be concerning to teachers because it is indicative of a lack in terms of the critical analytic skills which are required to use wbmt tools effectively as language learning tools. While this is undoubtedly a concern in any context, it may be particularly troubling in contexts such as Korea where such skills are seldom emphasized in the public English education system (Lee, Lee, Makara, Fishman, & Hong, 2014;Baek, 2016).…”
Section: Research Question 3: Identification Of Wbmt Output Errorsmentioning
confidence: 99%
“…With such research questions, explorative in nature, we adopted a qualitative approach, as suggested for these type of situations when the appraisal is not confirmatory (Lehmann et al, 2011) and when the behaviour to be investigated might vary across cultures (Lee et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…However, the consideration of students as consumers has not always being seen as beneficial for HEIs (Eagle & Brennan, 2007). As Mark (2013, pp. 2) stated "Although there is evidence that postsecondary students benefit from being treated like customers, the progress toward a universal adoption of a studentcustomer paradigm has been slow".In fact, the education service has always offered valuable outcomes for marketing and consumer behaviour researchers (Lee et al, 2015), but given the changes in the rationales. environments, providers and delivery methods of the Higher Education, it is important to constantly revisit the definition and ensure that the meaning of Higher Education service reflects current changes and challenges of modern context.…”
Section: Higher Education Service and Higher Education Managementmentioning
confidence: 99%
“…Their self-efficacy also depended on gender. Lun, Fischer, and Ward (2010) and Lee, Lee, Makara, Fishman, and Hong (2014) discovered that most of the Asian university students had lower critical thinking ability compared to the students who come from the West. One of the factors that might contribute to this issue was students' limited opportunity to perform their critical and creative thinking skills.…”
Section: Introductionmentioning
confidence: 99%